Emotional literacy programs for nurse managers: a scoping review protocol - Catarina Porfírio; Inês Moreira; Mauro Mota; Carlos Sequeira; Margarida Reis Santos; Regina Pires (Millenium, 2025)
Introduction: Nurse managers with emotional competences recognise, understand and manage their own emotions and those of the professionals they lead, contributing to a work environment conducive to excellent practice. Learning the emotional skills that enable you to be emotionally competent is emotional literacy. The development of emotional literacy programmes for nurse managers is fundamental to optimising nursing management.